Human pluripotent stem cells in regenerative medicine: where do we stand?. Issue 5 (November 2018) - Nguyen, Ha Thi; Jacobs, Kurt; Spits, Claudia
Abstract : Human pluripotent stem cells have the capacity to self-renew indefinitely and the ability to differentiate into all cell types of a human body. These characteristics instill them with an enormous promise in regenerative medicine, where they could be used in cell, tissue and even organ-based replacement therapy. In this review, we discuss their potential clinical applications and the advantages and pitfalls for the different types of human pluripotent stem cells to transition from the bench to the bedside. We provide an overview of the current clinical trials, and the specific challenges we are still facing, including immune compatibility, suboptimal differentiation, risk of tumor formation and genome instability.